PENGARUH FASILITAS BELAJAR TERHADAP MOTIVASI BELAJAR SISWA KELAS III SD NEGERI NOTOREJO KECAMATAN GONDANG KABUPATEN TULUNGAGUNG - Eko Purnomo; Fajrin Rizqy Ana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Learning facilities refers to the facilities and infrastructures utilized to support the learning activities in order to achieve the goals of education. Motivation is a condition that encourages someone to do an activity so that he can achieve his goals. This research utilized a quantitative research method, namely ex post facto research. The data were analyzed by using the prerequisite test and t-test. The conclusion of the t-test revealed that the score of tcount (3.681) > ttable (1.706) with a significance of 0.001≤0.05. Therefore, H0 was rejected and Ha was accepted. Thus, it can be concluded that learning facilities affected the learning motivation of grade III students at SDN I Notorejo, Kecamatan Gondang, Kabupaten Tulungagung in the academic year 2018/2019. The results of this research were used as an effort to improve the quality of learning, especially in the availability of adequate learning facilities as a supporting factor to increase the students’ learning motivation